2022
DOI: 10.1097/md.0000000000028894
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion for anorexia in COVID-19

Abstract: Background: As the outbreak of coronavirus disease 2019 , caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has rapidly spread over the world, the World Health Organization has declared the outbreak of COVID-19 an international public health emergency. Besides typical respiratory symptoms and signs of COVID-19, digestive symptoms and liver injury have been frequently reported during the course of the disease. The purpose of this study was to evaluate the efficacy and safety of moxibustion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…Some researchers have explored the safety and effectiveness of acupuncture in the treatment of patients with long COVID through systematic reviews and meta-analyses based on the related symptoms of long COVID [114] . At present, some researchers are planning to further explore acupoint stimulation therapy for patients with long COVID, and design research programs that can generate higher-level evidence involving improvements in taste abnormalities [115] , anorexia [116] , functional dyspepsia [74] , diarrhea [18] and other symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have explored the safety and effectiveness of acupuncture in the treatment of patients with long COVID through systematic reviews and meta-analyses based on the related symptoms of long COVID [114] . At present, some researchers are planning to further explore acupoint stimulation therapy for patients with long COVID, and design research programs that can generate higher-level evidence involving improvements in taste abnormalities [115] , anorexia [116] , functional dyspepsia [74] , diarrhea [18] and other symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Its medicinal characteristics are attributed to its active ingredients, including volatile oil, terpenes, flavonoids and phenolic acids (Cui et al 2022 ). Moreover, recent studies have shown that moxibustion, a medicinal product made from A. argyi leaves, played a crucial role in the prevention and treatment of Corona Virus Disease 2019 (COVID-19) (Teng et al 2020 ) and the prognostic treatment of splenic and pulmonary weakness during the convalescence (Wang et al 2022 ). Therefore, research on A. argyi focuses mostly on the analysis of medicinal ingredients and the identification of their functions.…”
Section: Introductionmentioning
confidence: 99%